Post-mortem magnetic resonance imaging with computed tomography-guided biopsy for foetuses and infants: a prospective, multicentre, cross-sectional study - Christoph Martin Rüegger; Dominic Gascho; Peter Karl Bode; Elisabeth Bruder; Christian Haslinger; Steffen Ross; Kevin Schmid; Claudia Knöpfli; Lisa J. Hofer; Leonhard Held; Rosa Maria Martinez; Hans Ulrich Bucher; et al. (BMC, 2022)
Abstract Background Post-mortem imaging has been suggested as an alternative to conventional autopsy in the prenatal and postnatal periods. Noninvasive autopsies do not provide tissue for histological examination, which may limit their clinical value, especially when infection-related morbidity and mortality are suspected. Methods We performed a prospective, multicentre, cross-sectional study to compare the diagnostic performance of post-mortem magnetic resonance imaging with computed tomography-guided biopsy (Virtopsy®) with that of conventional autopsy in foetuses and infants. Cases referred for conventional autopsy were eligible for enrolment. After post-mortem imaging using a computed tomography scanner and a magnetic resonance imaging unit, computed tomography-guided tissue sampling was performed. Virtopsy results were compared with conventional autopsy in determining the likely final cause of death and major pathologies. The primary outcome was the proportion of cases for which the same cause of death was determined by both methods. Secondary outcomes included the proportion of false positive and false negative major pathological lesions detected by virtopsy and the proportion of computed tomography-guided biopsies that were adequate for histological examination. Results Overall, 101 cases (84 fetuses, 17 infants) were included. Virtopsy and autopsy identified the same cause of death in 91 cases (90.1%, 95% CI 82.7 to 94.5). The sensitivity and specificity of virtopsy for determining the cause of death were 96.6% (95% CI 90.6 to 98.8) and 41.7% (95% CI 19.3 to 68.0), respectively. In 32 cases (31.7%, 95% CI 23.4 to 41.3), major pathological findings remained undetected by virtopsy, and in 45 cases (44.6%, 95% CI 35.2 to 54.3), abnormalities were diagnosed by virtopsy but not confirmed by autopsy. Computed tomography-guided tissue sampling was adequate for pathological comments in 506 of 956 biopsies (52.7%) and added important diagnostic value in five of 30 cases (16.1%) with an unclear cause of death before autopsy compared with postmortem imaging alone. In 19 of 20 infective deaths (95%), biopsies revealed infection-related tissue changes. Infection was confirmed by placental examination in all fetal cases. Conclusions Virtopsy demonstrated a high concordance with conventional autopsy for the detection of cause of death but was less accurate for the evaluation of major pathologies. Computed tomography-guided biopsy had limited additional diagnostic value. Trial registration ClinicalTrials.gov (NCT01888380).